ISSUES OF STUDENTS MOTIVATION IN FOREIGN LANGUAGE CLASSES - Olena Ye. Beresten; Karyna V. Yurchenko; Pavlo S. Saveliev (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
Motivation of students plays one of the most important roles in the effective study of a foreign language. If he is not motivated, the student is inattentive in class, does not do homework and may even distract others. Therefore, the key to successful learning a foreign language directly depends on the presence of certain motivation in students. In the proposed study, the authors aimed to analyze the main methods of creating, maintaining or strengthening the motivation of students while learning a foreign language. To achieve this goal, we used methods of generalization, systematization and selection of facts and materials obtained in the process of processing domestic and foreign bibliographic sources. Before presenting methodological developments, researchers turned to domestic and foreign authors who have dedicated their work to this issue. During the bibliographic analysis it was found that the chosen topic was thoroughly studied by such authors as: N. Arestova, A. Maslow and H. Heckhausen. All researchers agree that motivation is a set of motives that significantly affect any human activity in general and the study of a foreign language in particular. The authors offer the game as one of the most important methods to increase student motivation. We are currently considering a “station” game, which aims to create a product: an interview, a dialogue, a sketch or a role-playing game. Skills of teamwork, making extraordinary decisions are developed. The game “station” provides action-oriented, creative learning, which aims to reveal the personality. In the process of free labor, knowledge is formed that is of great importance for language practice. The form and method of execution the student chooses, which certainly increases the efficiency of the process. According to the authors, the game provides internal differentiation, as some stations offer materials for “weak” and “strong” students, which is extremely important because the group often includes applicants with different levels of foreign language proficiency. The game is based on the principles of the lesson, focused on creating a project, because the result of the task is not the only right solution, but alternatives. Thus, the game “station” provides action-oriented, creative learning, which aims to create a product such as a collage or poster. The main thing is that the student at each station finds a new learning approach and, performing tasks, improves their knowledge on this topic. It should be noted that such a result can be reached if the proposed tasks are of interest to the student, stimulate active work with materials and find a common solution to the problem. In addition, the method of using video stories in the classroom is considered as the main means of increasing student motivation. It is noted that the most important advantage of using video materials in education is the development of various types of mental activity, especially attention and memory. While watching videos in the audience there is an atmosphere of joint cognitive activity. These types of exercises provide an opportunity to increase motivation to learn foreign languages, significantly replenish the vocabulary of applicants and diversify classes. Watching videos is not only a source of information, but also contributes to the development of attention and memory of students, and has a positive effect on the strength of the assimilation of local lore and language material. In addition, such exercises pleasantly change the lesson, add to it elements of real life, even on the screen, but will teach you to work with videos, and not just look at the screen. It is concluded that video exercises are very diverse and serve not only to arouse cognitive interest in the subject, but also to improve the quality of knowledge acquisition and create a stable motivational base for learning a foreign language. During the study, the authors came to the following conclusions: a significant increase in student motivation to learn a foreign language is influenced by the use of unusual games, video and the use of modern applications aimed at successfully learning new vocabulary, such as Lexilize flashcards, 2 Books. All these methods together provide a high level of motivation for students in a foreign language class and contribute to its successful learning.